Comparative study of two Lotus species: Phytochemistry, cytotoxicity and antioxidant capacity - Ahmed M. M. Youssef; Zeinb A. S. EL-Swaify; Doaa A. M. Maaty; Mohamed M. Youssef (Journal of Pharmacy & Pharmacognosy Research, 2020)
Context: Phenolic and flavonoid compounds present in Lotus arabicus and L. glaber have not been identified yet. Also, no reports are demonstrating the cytotoxic and antioxidant activities of both lotus species. Therefore, it is interesting to study the anticancer effects and antioxidant capacity of them.